2019
DOI: 10.1039/c9nr01651a
|View full text |Cite
|
Sign up to set email alerts
|

Formation of silicate nanoscrolls through solvothermal treatment of layered octosilicate intercalated with organoammonium ions

Abstract: Silicate nanoscrolls with crystalline walls were prepared by intercalation of layered octosilicate with organoammonium ions and the subsequent solvothermal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…In summary, this study demonstrated the formation and the support the property of nanoscroll-supported platy particles by focusing on the incomplete rolling-up of kaolinite layers. Given the successful presence of Ag nanoparticles in the tubular interior of nanoscrolls at the edge of the kaolinite in this study and nanoscrolls with varied compositions, 1,9–12 the present results paved the way for the preparation and utilization of nanoscroll-supported platy particles.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In summary, this study demonstrated the formation and the support the property of nanoscroll-supported platy particles by focusing on the incomplete rolling-up of kaolinite layers. Given the successful presence of Ag nanoparticles in the tubular interior of nanoscrolls at the edge of the kaolinite in this study and nanoscrolls with varied compositions, 1,9–12 the present results paved the way for the preparation and utilization of nanoscroll-supported platy particles.…”
Section: Discussionmentioning
confidence: 59%
“…Various elds have widely investigated the fundamental properties and practical applications of nanotubes and nanoscrolls. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In addition to their functionalities induced by components, such as carbon and titania, one-dimensional and hollow morphology have been utilized to improve the composite mechanical properties and introduce molecules and nanoparticles to tubular interiors; concerning the latter use, nanotubes and nanoscrolls were used as supports. [1][2][3][4][5][6][7][8][9][10] Layered compounds comprising stacked ca.…”
Section: Introductionmentioning
confidence: 99%
“…For the synthetic hydrous layered silicate ilerite the formation of NS could be observed by ion-exchange with dioctadecyldimethylammonium followed by a solvothermal treatment for 1 day in heptane without prior delamination. [18] However, the yield was low as the authors outlined. Ionexchange with an excess alkyl ammonium salt led to intersalination and it was hypothesized that during solvothermal treatment the excess of intercalated salt is extracted one-sided exerting a steric pressure in the still intersalinated interlayers.…”
Section: Introductionmentioning
confidence: 98%
“…For the synthetic hydrous layered silicate ilerite the formation of NS could be observed by ion‐exchange with dioctadecyldimethylammonium followed by a solvothermal treatment for 1 day in heptane without prior delamination [18] . However, the yield was low as the authors outlined.…”
Section: Introductionmentioning
confidence: 99%
“…Many semiconductor materials such as oxides, oxynitrides, sulphides, phosphides, carbides and noble metals are used either as catalysts or co-catalysts to enhance photocatalytic hydrogen evolution efficiency. 1–5 The use of nanostructured materials, isolated atoms, composites with suitable band alignment, optical band gap engineering by doping, etc. accelerates the charge transfer process and reduces the possibility of electron–hole recombination, and hence increases the overall efficiency of a photocatalytic process.…”
Section: Introductionmentioning
confidence: 99%